PENINGKATAN MANAJEMEN DAN TEKNOLOGI PEMASARAN PADA UMKM OJESA (OJEK SAHABAT WANITA) DALAM MENGATASI LESS CONTACT EKONOMI MASA COVID-19 - Ruslaini, Ruslaini; Abizar, Abizar; Ramadhani, Nina; Ahmad, Imam (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Ojesa (Ojek Sahabat Wanita) is an online motorcycle start-up business specifically targeted for women in the city of Bandar Lampung. Like any other startup business, Ojesa has experienced several obstacles, especially in the aspects of management and application being used; these obstacles have been a bigger challenge during the Covid-19 period. Among the challenges were the absence of planning, organizing, actuating, and controlling (POAC) functions as well as the break down of the serverÂ  which made the drivers of Ojesa experienced obstacles in communicating with consumers. The purposes of method of the activities were carried out to explore problems, to find out the urgent less contact problems in the economy during the Covid period, to conduct training and assistance in the aspects of management and marketing technology. These activities have resulted in the implementation of the management function (POAC) in the activity and recording plan, and it eventually launched new products. The upgrade Ram is set unlimited so that the consumers' demands can be served properly, automatically and in real time. There is a more integrated marketing technology development system. Also, there is an improvement in skills and management for its human resources so that they can serve customers in a friendlier, more patient and gentle manner and in the future it is expected to have a solid team and professional human resources.